Prevention of Incident Hypertension in Patients With Obstructive Sleep Apnea Treated With Uvulopalatopharyngoplasty or Continuous Positive Airway Pressure: A Cohort Study - Lin, Yi-Chih; Chen, Chun-Tien; Chao, Pin-Zhir; Chen, Po-Yueh; Liu, Wen-Te; Tsao, Sheng-Teng; Lin, Sheng-Feng; Bai, Chyi-Huey (Frontiers in Surgery, 2022)
Purpose To determine whether treatment with uvulopalatopharyngoplasty (UPPP) or continuous positive airway pressure (CPAP) in patients with obstructive sleep apnea (OSA) prevents hypertension, compared to those not receiving any treatment. Methods A retrospective cohort study was conducted among 413 patients with OSA (age ≥ 35 years) at the Shuang Ho Hospital between 2009 and 2016. The patients were divided into three groups: UPPP, CPAP, and non-treatment groups. Data about the personal characteristics, history of comorbidities, and polysomnography (PSG) reports were collected at baseline. A Cox model with inverse probability of treatment weighting was used to adjust for confounders and baseline diversity. Results After multivariate adjustment and weighting for incident hypertension, patients in both the CPAP and UPPP groups showed a significant preventive effect on hypertension than in the non-treatment group. Moreover, patients in the CPAP group had lower event rates than those in the UPPP group. Conclusion UPPP can prevent the development of new-onset hypertension in patients with OSA. CPAP had a better preventive effect than UPPP. UPPP might be a good alternative for reducing the risk of the onset of hypertension when compliance to CPAP is poor.